2000
DOI: 10.1080/15257770008033040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Activity of C-5 Substituted Analogues of D4T Bearing Methylamino- or Methyldiamino-Linker Arms

Abstract: A general strategy is reported for the preparation of C-5-methylamino- or methyldiamino-d4T analogues of "different sizes". Reactions of the 2',3'-didehydro-2',3'-dideoxy-C-5 hydroxymethyl precursor (7) with either polymethylene diamines (n = 6, 8, 10 and 12) or propargylamine proceed regioselectively via substitution reactions at the C-5 position of uracil. The compounds were evaluated for antiviral activity and cytotoxicity. No significant activity was observed for compounds 9, 11, and 13, but 10 and 12 exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Along with others, these two studies depict the complex structure-activity relationship that exists for putative bifunctional inhibitors, but a promising finding demonstrated that a linkage at the 5-position of d4T with a methylamino linker did not perturb activity of the NRTI in cell culture 14 . This contrasts with data from Gavriliu et al, which argues attachment of this methylamino linker indeed disrupts d4T’s antiviral activity in culture 25 . Comparison of these two studies yields significant differences in the linker terminus, further supporting the complexity in addressing linkage position and linker design for an RT bifunctional inhibitor.…”
contrasting
confidence: 91%
See 1 more Smart Citation
“…Along with others, these two studies depict the complex structure-activity relationship that exists for putative bifunctional inhibitors, but a promising finding demonstrated that a linkage at the 5-position of d4T with a methylamino linker did not perturb activity of the NRTI in cell culture 14 . This contrasts with data from Gavriliu et al, which argues attachment of this methylamino linker indeed disrupts d4T’s antiviral activity in culture 25 . Comparison of these two studies yields significant differences in the linker terminus, further supporting the complexity in addressing linkage position and linker design for an RT bifunctional inhibitor.…”
contrasting
confidence: 91%
“…Substitution at both N-3 and C-5 of AZT (Retrovir) has lead to inactive antiviral compounds 11 . The substitutions at C-5 in d4T (stavudine, Figure 1) yield mixed results, but mostly result in inactive analogs 14,25,2830 . Attempted modifications to AZT and d4T suggest the difficulty for human thymidine kinase (hTK) to phosphorylate 2′,3′-dideoxythymidine analogs, but there is evidence that C-5 substituted thymidine can be phosphorylated in vivo by thymidine kinase 3133 .…”
mentioning
confidence: 99%
“…To overcome these practical limitations, we designed an alternative f 5 C monomer in which the reactive formyl group is appropriately masked. Riml and Micura reported the synthesis and incorporation of a hm 5 C monomer into RNA ONs; their route provides this monomer in a 3 % overall yield in eight steps from 5‐hydroxymethyluridine (hm 5 U), which itself is obtained in a three‐step synthesis from uridine, and this brings the total number of steps to 11 . We therefore, at the same time, considered the development of a faster and more efficient route to this monomer.…”
Section: Methodsmentioning
confidence: 99%
“…Riml and Micura reported the synthesis and incorporation of a hm 5 C monomer into RNA ONs; their route provides this monomer in a 3% overall yield in eight steps from 5-hydroxymethyluridine (hm 5 U),[15] which itself is obtained in a three-step synthesis from uridine, and this brings the total number of steps to 11. [17] We therefore, at the same time, considered the development of a faster and more efficient route to this monomer. The presence of the 2′-hydroxy group makes the synthesis and incorporation of functionally modified ribonucleoside phosphoramidites particularly challenging compared to that of the analogous DNA phosphoramidite.…”
mentioning
confidence: 99%
“…Some β- L -2′,3′-didehydro-2′,3′-dideoxythymidine (β- L -d4T) analogues ( Figure 3 , 7a ) have been synthesized, all bearing a tether on the C-5 position of the uracil ring, and they were evaluated in vitro for anti-HIV-1 activity [ 40 ]. The results revealed that the L -d4T derivative, containing 12 methylene units at the 5-position, displayed some activity in the CEM-SS cells (IC 50 2.3 µM), probably due to the more lipophilic nature of the nucleoside.…”
Section: Nucleoside Analogs As Therapeutic Antiviral and Antitumor Agentsmentioning
confidence: 99%